Platelet-rich plasma (PRP) on orthopedic clinical daily practice: a literature review - Anthony Gunawan; Anak Agung Ngurah Ronny Kesuma; I Komang Agus Krisna Saputra¬¬; I Komang Mahendra Laksana (Intisari Sains Medis, 2022)
The use of PRP (platelet-rich plasma) is beneficial and even more important in the future. The most common indications were tendon damage (77%), osteoarthritis (68%), muscle damage (57%) and cartilage damage (51%). It is a purified autologous blood product with a higher platelet concentration than whole blood. It is rich in various cytokines and growth factors and has been shown to initiate and enhance healing by stimulating cell migration, cell proliferation, angiogenesis, and matrix synthesis. In rotator cuff injury, PRP injection led to significant long-term pain relief but not in functional improvements. In Osteoarthritis, PRP injection is associated with long-term pain relief and function improvements. PRP injection has a better outcome in VAS (visual analog scale) and DASH (The Disabilities of the Arm, Shoulder and Hand) scores in elbow ulnar collateral ligament pathologies, including lateral elbow epicondylitis. In medial epicondylitis, a paucity of studies causing therapeutic modality for PRP has not yet been established. In acute muscle injury, PRP used has no differences in imaging, pain, ROM (range of motion), muscle strength, and muscle function. In Achilles Tendinopathy, PRP injection has been associated with improvement in VAS, but no difference in VISA-A (The Victorian Institute of  Sports Assesment – Achilles Questionnaire) score. However, the majority of published literature is secondary and tertiary evidence. Future studies could provide important information about the optimal concentrations of growth factors, platelets and leukocytes required for the desired effect in many specific tissues, as well as the appropriate method of administration and timing of drug application.